(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
This article explores the role of note-taking systems in enhancing interpreter performance, particularly in consecutive and simultaneous interpreting. Effective interpretation requires not only strong linguistic competence, but also advanced cognitive skills such as memory retention, attention management, and rapid information processing. Note-taking serves as a crucial support tool that helps interpreters capture key ideas, structure information, and reduce cognitive overload during interpretation tasks.